The Production of Superior Hybrid Jawa Super Chicken as a Food Security Strategy During COVID-19 Pandemic in Ngoro-Oro Village, Patuk, Gunung Kidul, Yogyakarta - Hendry Saragih; Ardaning Nuriliani; Yuny Erwanto; Adi Susanto; Sari’ah Cintami Damayanti; Bima Mahendra; Flaﬁani Cios Conara; Lailly Tsania Nur Hidayah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2022)
During the COVID-19 outbreak, economic sectors slowed down and caused a signiﬁcant impact on almost any level of society, especially the middle to lower class income. Thus, a strategy needs to be developed to overcome this situation. The Ngoro-Oro Village has potency in the livestock sector, especially in the development of superior hybrid Jawa super chicken. Therefore, the purposes of our community service in the Ngoro-Oro Village were to develop superior hybrid Jawa super chicken and use black soldier ﬂy larvae as an alternative feed for chicken. We distributed 105 Jawa super hens aged ± three months and 21 superior free-range roosters. Furthermore, the hens and rooster were mated at the age of ± six months with a ratio of 5:1. The hybrid chickens were evaluated for their body weight and morphometric measurements until the age of four months. We also monitored the farmer community’s use of black soldier ﬂy larvae as an alternativ e feed for chickens. The hybrid chicken at the age of 4 months old has a body weight of about 971.64 ± 271.06 grams with a height of about 41.73 ± 5.87 cm, head’s length of 5.01 ± 0.44 cm, body length of 22.82 ± 3.14 cm, body width of 10.68 ± 1.49 cm, wing’s length 19.14 ± 2.67 cm, thigh’s length 11.95 ± 1.71 cm, and leg’s length is about 7.91 ± 1.41 cm. Moreover, Ngoro-Oro farmers can improve the community’s economy by selling superior hybrid Jawa super chicken at a price 75,000 – 85,000 rupiahs per head. Through all of this community service program, it could be concluded that superior hybrid Jawa super chicken is potential to be developed as broiler, and the farmer community could develop black soldier ﬂy larvae as an alternative feed for chicken.